Induced Mutation on Jatropha (Jatropha Curcas L.) for Improvement of Agronomic Characters Variability - Ita Dwimahyani; . Ishak (PPIKSN-BATAN, 2004)
Induced mutation can be used for improving quality in term of seed production, oil content in seed and early maturity of Jatropha with the aim for bio_diesel in Indonesia. The doses of 10, 15,20, and 25 Gy of gamma applied to cuttings was able to increase genetic variability in vegetatively propagated plants of Jatropha at M1V1 (mutant-vegetative-1) generation. Selection for desirable trait will be done at M1 V2 (mutant-1 and vegetative-2) generation untill homogenous plants obtained. Gamma rays at dose of 20 to 25 Gy damaged several genes controlling growth and development on Jatropha which was shown by dwarf and poor plant growth compared to control (plant without irradiation). Irradiation with the dose of 10 Gy raised genetic variability on plant development which was identified with early maturity, 100 seeds weight was 30% over control, and the number of branch growth was good